2016
DOI: 10.1167/iovs.16-19355
|View full text |Cite|
|
Sign up to set email alerts
|

A Swine Model of Selective Geographic Atrophy of Outer Retinal Layers Mimicking Atrophic AMD: A Phase I Escalating Dose of Subretinal Sodium Iodate

Abstract: The swine model of a controlled area of circumscribed retinal damage, with well-delimited borders, and selectively of the outer layers of the retina presented herein shows several clinical and histologic features of geographic atrophy in AMD. Therefore, it may represent a valuable tool in the investigation of new emerging regenerative therapies that aim to restore visual function, such as stem cell transplantation or optogenetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 33 publications
1
41
0
2
Order By: Relevance
“…17,20 Recently, it was further shown that photoreceptors and RPE die through distinct mechanisms, the former through apoptosis and the latter through necroptosis. 21 In a swine model, subretinal blebs of NaIO 3 were shown to induce dose-dependent damage to the outer neuroretina and alterations to the RPE/Bruch's complex as shown by SD-OCT. 22 However, since BAF was not used in that study, a direct comparison at the RPE level with the present study cannot be done.…”
Section: Discussionmentioning
confidence: 79%
“…17,20 Recently, it was further shown that photoreceptors and RPE die through distinct mechanisms, the former through apoptosis and the latter through necroptosis. 21 In a swine model, subretinal blebs of NaIO 3 were shown to induce dose-dependent damage to the outer neuroretina and alterations to the RPE/Bruch's complex as shown by SD-OCT. 22 However, since BAF was not used in that study, a direct comparison at the RPE level with the present study cannot be done.…”
Section: Discussionmentioning
confidence: 79%
“…Following stimulation with human vitreous or fibronectin, RPE cells differentiate and migrate to the vitreous body (12,13). RPE cells proliferate and secrete molecules into the extracellular matrix (ECM), resulting in formation of periretinal membrane with contraction ability, leading to retinal detachment (14,15). Inflammatory cytokines may be involved in ECM function and cell proliferation; therefore, it was hypothesized that inflammatory cytokines affect ECM, induce abnormal proliferation of RPE cells and contribute to the development of RRD (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…13,22 In addition, exposure of the RPE cells to NaIO 3 induces a loss of the integrity of the RPE cells and an enlargement of RPE cells. 13,23 Although a dysfunction of the RPE cells leads to a reduction in vision, 24 the time-dependent changes in the RPE morphological and physiological changes have not been determined.…”
mentioning
confidence: 99%